TRANSLATION UNITS - Ergasheva Khusnida; Akhmedov Azimjon (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation. Unit Of Translation - The smallest entity in a text that carries a discrete meaning. It varies all the time, ranging from individual words through phrases and sentences right up to entire paragraphs. This article